Rhinosporidiosis: A Rare Cause of Proptosis and an Imaging Dilemma for Sinonasal Masses. (30th November 2016) - Dey, Amit Kumar; Sharma, Rajaram; Mittal, Kartik; Kumar, Puneeth; Murumkar, Vivek; Mitkar, Sumit; Hira, Priya
Abstract : Background. Rhinosporidiosis is a common disease entity in tropical countries; however, it can be encountered in other parts of the world as well due to increasing medical tourism. It may mimic other more malignant and vigorous pathologies of the involved part. Case Report. We present a case of a 36-year-old male presenting with proptosis due to involvement of nasolacrimal duct which is rare. We will discuss typical CT and MRI features of the disease which were present in the case. Conclusion. For a surgeon and a radiologist, this is a necessary differential to be kept in mind for sinonasal masses. CT and MRI are invaluable investigations. However, FNAC is confirmatory. Both clinical and radiological aspects are required to reach correct diagnosis.